Built environment: the sustainability of heritage - Silva, J.A.R. Mendes da (2010)
Different sustainable evaluation tools can provide a way to certify the building¬¬`s performance during its life cycle: raw material depletion, production of materials and components, construction, use and demolition. In this process, several variables that analyze common components, such as the reduction of resources consume, the reuse and recycle potential, flexibility and adaptability, the pollution components generated during the process, are involved. Some examples of these tools are the systems like SBTool, BREEAM, BEE or LiderA that are used to evaluate a specific context according to specific conditions. Meanwhile, the existing evaluation systems are oriented to the building´s design phase or have under consideration patterns adapted to the 21st century reality. This work was developed due to the need to analyse and evaluate the built environment, specifically in what concerns the urban settlements in Portuguese cities, with more than three hundred years old, and that are not enclosed in the new construction’s reality - both at materials and techniques levels. The knowledge gathered about the built environment allows the creation of a sustainable grid capable of guide-lining rehabilitation actions. The evaluation of these urban areas was carried out based on an exhaustive work of collecting the building’s characteristics, in an area with around 770 buildings, allowing the creation of a built environment sustainability evaluation grid and adapted to socio, cultural, heritage, economic and environmental contexts. The grid mentioned before was designed after a set of parameters were analyzed, such as: i) the existent materials and the constructive solutions adopted; ii) the urban mesh and the meeting of the construction resources to the built environment; iii) the contemporaneous patterns and the possibilities of reusing; iv) the heritage and cultural values; v) the social and economic values. The evaluation grid presented in this work shows a set of different parameters, where the criteria that are related to the external environment are reassessed according to the existent urban possibilities and where the criteria related to internal environment are adapted to the existent spaces’ possibilities.